Development of tonality and consonance categorization ability and preferences in 4- to 6-year-old children - Will, Johanna Karoline; Roeske, Christina; Degé, Franziska (Frontiers in Psychology, 2024)
Consonance perception has been extensively studied in Western adults, but it is less clear how this perception develops in children during musical enculturation. We investigated how this development occurs in 4- to 6-year-old children by examining two complex musical skills (i.e., consonance and tonality preferences). Accordingly, we developed a child-focused approach to understand the underlying developmental processes of tonality and consonance preferences in 4- to 6-year-old children using a video interview format. As previous studies have confounded preference with perception, we examined each concept separately and measured perceptual abilities as categorization. For tonality, the ability to categorize tonal and atonal melodies developed by the age of 6 years. It is noteworthy that only children who could categorize successfully showed a preference for tonality at the age of 6. For consonance, we observed an early preference for consonance at 4 years of age, but this preference was only measurable with large differences between consonant and dissonant stimuli. We propose that tonality and consonance preferences develop during childhood with increasing categorization ability when the surrounding musical culture is marked by Western tonality and consonance.